2010
DOI: 10.1099/vir.0.020750-0
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of highly pathogenic avian H5N1 influenza viruses and the emergence of dominant variants

Abstract: Highly pathogenic avian H5N1 viruses have circulated in South-east Asia for more than a decade and have now spread to more than 60 countries. The evolution of these viruses is characterized by frequent reassortment of the so-called ‘internal’ genes, creating novel genotypes. Additionally, over time, the surface glycoprotein, haemagglutinin (HA), which is the primary target of the adaptive immune response, has evolved by point mutation into 20 genetically and potentially antigenically distinct clades. To invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 53 publications
0
24
0
2
Order By: Relevance
“…On: Fri, 11 May 2018 14:48:59 H5N1 virus have frequently reassorted with other subtypes of avian influenza viruses circulating in poultry (Neumann et al, 2010;Zhao et al, 2008). In particular, H5N5, H5N8 and H5N2 subtypes bearing the genetic backbone of clade 2.3.4 H5N1 viruses have been identified in poultry populations (Gu et al, 2011;Zhao et al, 2012;Wu et al, 2014).…”
mentioning
confidence: 99%
“…On: Fri, 11 May 2018 14:48:59 H5N1 virus have frequently reassorted with other subtypes of avian influenza viruses circulating in poultry (Neumann et al, 2010;Zhao et al, 2008). In particular, H5N5, H5N8 and H5N2 subtypes bearing the genetic backbone of clade 2.3.4 H5N1 viruses have been identified in poultry populations (Gu et al, 2011;Zhao et al, 2012;Wu et al, 2014).…”
mentioning
confidence: 99%
“…Descendants of these Qinghai Lake-like viruses spread into Europe and Africa, thus establishing the Eurasian-lineage Z viruses (clade 2.2) (5,(12)(13)(14)(15). Strikingly, the Qinghai Lake isolates and descendants possessed Lys at amino acid position 627 (627K) on the polymerase basic 2 (PB2) protein, a motif previously associated with adaptation to mammals (10,11,16).…”
mentioning
confidence: 99%
“…Subgenotype Z.2 comprises viruses isolated in Thailand and Vietnam, whereas most subgenotype Z.3 viruses have been isolated in Indonesia. The three subgenotypes are characterized by phylogenetically distinguishable polymerase (PB2, PB1, and PA) genes (8). In addition, the NS1 protein of subgenotype Z.1 viruses differs by several amino acids from that of subgenotype Z.2 and Z.3 viruses (8).…”
mentioning
confidence: 99%
“…Since 2003, these viruses have become enzootic in poultry populations in several parts of the world and have evolved rapidly through reassortment and point mutations (1)(2)(3)(4)(5)(6)(7)(8)(9). Recently, we carried out a comprehensive phylogenetic analysis of the genes that encode the internal proteins (i.e., the PB2, PB1, PA, NP, M, and NS genes) of HPAI H5N1 viruses isolated from 2000 to 2008 and found that viruses of the so-called genotype Z (6,10), which was first reported in 2002, have since diverged into three subgenotypes, Z.1 to Z.3 (8). Subgenotype Z.1 includes the Qinghai Lake viruses (which caused an outbreak among wild aquatic birds at Qinghai Lake, China, in 2005 [11][12][13]) and their descendants, which have spread into Europe, Africa, and the Middle East.…”
mentioning
confidence: 99%